'Who you gonna call?' The role of trust and relationships in desistance from crime. (December 2014) - Rowe, Michael; Soppitt, Sarah
Motivation and engagement in desistance programmes are examined in an article that analyses two projects that aimed to 'normalize lifestyles' of chaotic offenders. In one of the projects, participants claimed that their engagement was related to the charitable sector of the provider, which meant that staff were outside of the parameters of offender management regimes. However, similar claims were made by participants in the other programme − which was delivered by statutory public sector agencies but by staff operating in different roles to the usual probation service framework. On this basis it is argued that the character, culture and ethos of programmes is of greater significance than their status in terms of third, public or private sectors.